Japan Studies and the Disciplines - Švambarytė, Dalia (Acta Orientalia Vilnensia, 2005)
Vilnius University Curriculum is a plan to foster a student’s academic development and to enhance an integration of various kinds of knowledge. The paper offers theoretical approaches to reexamining curricula of Japan Studies along the lines of area studies, cultural studies, language training, and interdisciplinarity. The problem of putting theory into practice is discussed on the basis of the Comparative Asian Studies programme at Vilnius University. This programme was designed to facilitate the goal of training individuals who combine thorough disciplinary and area specialization.